2013
DOI: 10.3855/jidc.3867
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of clinical methicillin-resistant Staphylococci isolates to new antibiotics

Abstract: Background: The treatment of methicillin-resistant staphylococcal infections has been a growing problem both in and out of hospitals for the past 30 years. Therefore, there is a need for other antibiotics as an alternative to glycopeptides in the treatment of methicillin-resistant staphylococcal infections. This study investigated the in vitro susceptibility of 49 methicillin-resistant Staphylococcus aureus (MRSA) and 59 methicillin-resistant coagulase negative staphylococci (MRCNS) clinical isolates to daptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(53 reference statements)
1
5
0
2
Order By: Relevance
“…Another study demonstrated that 2% of MRSA and 3% of methicillin-resistant coagulase-negative staphylococci were resistant to tigecycline [27]. A study in Iran reported a tigecycline-resistant MRSA strain for the first time in 2013 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that 2% of MRSA and 3% of methicillin-resistant coagulase-negative staphylococci were resistant to tigecycline [27]. A study in Iran reported a tigecycline-resistant MRSA strain for the first time in 2013 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Günümüzde MRSA enfeksiyonlarının tedavisinde klinikte kullanımda olan vankomisin ve teikoplanin olmak üzere iki glikopeptid grubu antibiyotikler ve 2000'li yıllardan sonra kullanıma giren linezolid, daptomisin ve tigesiklin gibi antibiyotiklere karşı direnç dünyada ve ülkemizde nadir olarak bildirilmiştir. [23][24][25][26][27][28] Çalışmamızda bu antibiyotiklere karşı direnç gözlenmemiştir.…”
Section: Discussionunclassified
“…Ülkemizde henüz kullanıma girmeyen fakat dirençli suşların bildirildiği yeni antibiyotiklerden biri de K/D'dir. Yapılan çalışmalarda Öksüz ve arkadaşları 14 Kullanıma giren yeni antibiyotiklere rağmen MRSA enfeksiyonla¬rında temel tedavi seçeneği glikopeptidlerdir. Glikopeptid direnci ilk kez 2002 yılında ortaya çıkmış olup, son yıllarda dünyanın değişik bölgelerinde giderek artan oranlarda VISA/hVISA izolatları rapor edilmektedir 16,17 .…”
Section: Discussionunclassified